Preschool Teachers’ Technology Acceptance During the COVID-19: An Adapted Technology Acceptance Model - Hong, Xiumin; Zhang, Mingzhu; Liu, Qianqian (Frontiers in Psychology, 2021)
Online education has become a major reaction to the COVID-19 epidemic, which requires preschool teachers to quickly adapt to online education and accept educational technology. In this emergency background, research on the preschool teachers’ technology acceptance provides clues to improve preschool teachers’ intention to use educational technology. The Technology Acceptance Model (TAM) is widely used to examine the process of individuals’ technology acceptance in the previous literature. Therefore, this study seeks to examine preschool teachers’ technology acceptance with the adapted TAM and their determinant factors. The proposed model was empirically validated by using survey data from 1,568 preschool teachers during the COVID-19. Results indicate that preschool teachers’ behavioral intention was moderate to high level. Perceived usefulness and perceived ease of use are direct significant predictors of preschool teachers’ behavioral intention. Perceived usefulness is affected by perceived ease of use and job relevance. Computer self-efficacy and perceptions of external control are the positive factors toward perceived ease of use. Our findings present powerful evidence for the applicability of the adapted TAM in a sample of Chinese preschool teachers under emergency circumstances. These results highlighted some potential avenues for interventions aimed at improving preschool teachers’ acceptance toward educational technology.